Influência do haleto/pseudohaleto na catálise de hidrogenação por complexos do tipo cis- [Ru(A)2(dppb)(N-N)] - Ribeiro, Murillo Cardoso (2013)
THE INFLUENCE OF HALIDE/PSEUDOHALIDE IN HYDROGENATION CATALYSIS BY COMPLEX CIS-[RU(A)2(DPPB)(N-N)]. Ruthenium complexes, with general formula cis-[Ru(A)2(dppb)(N-N)], (A = pseudohalides CN-, N3 - e SCN-) were obtained from the respective precursors cis- [RuCl2(dppb)(N-N)] {N-N= 2,2’- bipiridine (bipy), 4,4’-dimetil-2,2’-bipiridine (Mebipy) and 4,4’-dimetoxi-2,2’-bipiridine (MeObipy)} and dppb = 1,4-bis(difenilfosfina) butane, and characterized. These new Ru(II) complexes were characterized by analytical and spectroscopical techniques, such as Absorption Spectroscopy in the Infrared Region (IV) and Ultraviolet/Visible (UV/Vis), Nuclear Magnetic Ressonance (RMN), Molar Conductivity, X-ray Diffraction, Elemental Analisys, Cyclic Voltammetry (CV) and Differential Pulse Voltammetry (DPV). Catalytic studies were realized on cyclic hexene hidrogenation reaction using complexes with general formula cis-[RuCl2(dppb)(N-N)], for which the results have shown to be dependent of the utilized solvent in the process. In order to support data for a possible suggestion of and catalytic mechanism of the reaction involved in the process complexes containing pseudohalides were also studied in the same conditions. The fact that these complexes did not present catalytic activity is coherent with the inert properties of the pseudohalide complexes, with respect their dissociation from the Ru(II) center, considering their good π receptor properties, able to form strong bond with metallic centers, and also shown that during the catalytic cyclic the bidentate ligands (dppb and N-N) do not have their binding with the metal broken, which could allow the formation of a possible coordination center for the metal, able do bind the substrate, conducting to a catalytic process, which was not observed in these cases. The results obtained in the studies realized with the complexes cis-[RuCl2(dppb)(N-N)] allowed us to suggest that the substrat convertion follow two different pathways, depending of the used solvent in the process to be protonic and coordinating, but labile (alchools) or non coordinating (dichloromethane or acetone). Strong coordinating solvents, such as DMSO and CH3CN (S) did not present catalytic results, suggesting that the dissociation of the chloride from the complexes produce non catalytic species, such as cis-[RuCl(S)(dppb)(N-N)]Cl.